2014
DOI: 10.1037/spq0000055
|View full text |Cite
|
Sign up to set email alerts
|

Promoting social-emotional learning in adolescent Latino ELLs: A study of the culturally adapted Strong Teens program.

Abstract: The current study evaluated the effects of the culturally adapted Jóvenes Fuertes (Strong Teens) Social-Emotional Learning (SEL) program on the social-emotional outcomes of Latino English language learners (ELLs). A quasi-experimental design with random assignment by classrooms was used to assess the intervention's effects on students' knowledge of SEL and resiliency. A sample of 102 Spanish-dominant Latino ELLs enrolled in middle or high school participated in this study. The results indicated significant int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
71
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 37 publications
(68 reference statements)
5
71
0
1
Order By: Relevance
“…The majority of students (> 80%) reported the adapted intervention was appropriate and relevant for students at their school, with no significant differences between Hispanic and White students. Results are similar to research demonstrating the social validity of culturally adapted existing school-based interventions [39]. Thus, this study represents a first step in developing culturally appropriate brief, bullying bystander intervention for this population and adds to the literature supporting the social validity of culturally adapted schoolbased interventions.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The majority of students (> 80%) reported the adapted intervention was appropriate and relevant for students at their school, with no significant differences between Hispanic and White students. Results are similar to research demonstrating the social validity of culturally adapted existing school-based interventions [39]. Thus, this study represents a first step in developing culturally appropriate brief, bullying bystander intervention for this population and adds to the literature supporting the social validity of culturally adapted schoolbased interventions.…”
Section: Discussionsupporting
confidence: 77%
“…Because adapted interventions need to be grounded in the experiences of individuals who belong to the target cultural audience, it is important to include cultural group members as active participants in modifying intervention curriculum to be culturally relevant [35]. Achieving high levels of social validity (e.g., acceptability) is also important when establishing culturally responsive and effective interventions [39]. The ecology validity model provides one approach for helping to guide the adaption of existing interventions to be culturally appropriate [40].…”
Section: Culturally Appropriate Intervention Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…Equally important, this study revealed the SCT‐SSS had a positive effect on Hispanic ELL students' reading achievement scores (η p 2 = .12). This result is consistent with previous research results that cultural adaptations of existing evidenced‐based interventions can have a similar influence on Hispanic ELL populations (Castro‐Olivo, ; Castro‐Olivo & Merrell, ). Instruction in the students' first language may have helped students understand and practice the skills needed to improve their performance on the state standardized achievement tests in a safe and supportive classroom environment.…”
Section: Discussionsupporting
confidence: 93%
“…Results from previous SSS studies have indicated that when school counselors foster learning environments that are individualized, responsive, supportive, and encouraging, they can have a direct impact on students' academic and behavioral outcomes (Bowers et al, ; Brigman & Campbell, ; Brigman, Webb, & Campbell, ; Campbell & Brigman, ; Lemberger & Clemens, ; Lemberger et al, ; Mariani, Webb, Villares, & Brigman, ; Villares, Frain, Brigman, Webb, & Peluso, ; Webb, Brigman, & Campbell, ). Although the previous studies involved ethnic minority students, more research is needed to determine the impact of culturally translated SEL programs on English language learner (ELL) students' academic achievement (Castro‐Olivo, ; Rosenblatt & Elias, ). Therefore, in this article, we (a) provide an overview of the challenges Hispanic students face in education, (b) examine the role of the school counselor in promoting social‐emotional development, (c) describe the SSS curriculum and the Spanish Cultural Translation of the SSS (SCT‐SSS) classroom program, and (d) discuss results from a quasi‐experimental study conducted to determine the effectiveness of implementing the SCT‐SSS program to improve Hispanic and Hispanic ELL students' achievement scores.…”
mentioning
confidence: 99%